Penggunaan Kit Asas Membaca Bahasa Melayu untuk kanak-kanak pemulihan khas / Nurul Haniza Samsudin - Nurul Haniza , Samsudin (2017)
This research attempted to develop Basic Reading Kit for remedial education children in the learning of Malay language. This Basic Reading Kit contains a set of model, module, exercise book, story book and flash cards which are based on folklore themes. Levels of reading among the remedial education children are based on the three domains propagated in the Bloom’s Taxonomy: cognitive skills (the abilities to memorise, comprehend and apply), psychomotor skills (the abilities to imitate and manipulate), and affective skills (the abilities to recognise and respond). The effectiveness of the Basic Reading Kit in the learning of Malay Language was analysed based on three factors: Language learning, The usage of teaching aids, and skills of the remedial education children themselves. This research was a case study involving eight year three students undergoing remedial education class. The instruments used in this research include Reading Skills Assessment Test, psychomotor and affective skills checklist, and unstructured observation form. Quantitative data analysis was utilised in order to discover the cognitive, affective and psychomotor abilities. As for the unstructured observational data, qualitative analysis was employed. The researcher executed a between-method triangulation as to obtain the validity and reliability of the research. The research findings indicate that the ability to apply appears to be the most acquired cognitive skill among the subjects (99.58%), followed by the abilities to comprehend (95.36%) and to remember (95.8%). As for the psychomotor skills, the checklist analysis portrays that the imitation ability scored 81.67% in comparison with manipulative ability which scored 69.58%. Of the affective skills, the ability to respond (85.42%) outnumbered the ability to recognise (84.17%). The qualitative results highlight three factors contributing to the effectiveness of the Basic Reading Kit in the Malay Language learning - Language learning, The usage of teaching aids, and skills of the remedial education children themselves. Both the quantitative and qualitative data reveal the effectiveness of the Basic Reading Kit in enhancing the reading ability among remedial education children.